Analyzing the LCOE of Suralaya Coal-Fired Power Plant under Coal DMO and Market Price Scenarios - Razzaq Akbar Merbawan; Nur Aini Hidayati (Publikasi Indonesia, 2026)
Coal-fired power plants remain an important part of Indonesia’s electricity system because they provide large-scale and reliable baseload supply. However, the perceived low cost of coal-fired electricity is partly influenced by domestic coal pricing policy, particularly the Domestic Market Obligation (DMO) scheme. This study aims to estimate and compare the Levelized Cost of Electricity (LCOE) of the Suralaya coal-fired power plant under two coal price scenarios: the DMO price and the market price. A quantitative case study approach was applied using 2024 operational and financial data. The LCOE was calculated using an annualized cost approach by combining annualized capital cost, operation and maintenance cost, and fuel cost, then dividing total annual cost by annual net electricity generation. The results show that the LCOE based on the DMO coal price is IDR 1,008.58/kWh, while the LCOE based on the market price is IDR 1,049.52/kWh. The use of market price increases the LCOE by IDR 40.94/kWh, or 4.06%, compared with the DMO scenario. These findings indicate that coal pricing assumptions affect the financial interpretation of coal-fired power generation costs. Therefore, generation cost assessment should clearly distinguish between actual financial cost under domestic pricing policy and economic cost based on market price.